Sensitive cytometry based system for enumeration, capture and analysis of gene mutations of circulating tumor cells. Issue 3 (23rd February 2016) - Sawada, Takeshi; Watanabe, Masaru; Fujimura, Yuu; Yagishita, Shigehiro; Shimoyama, Tatsu; Maeda, Yoshiharu; Kanda, Shintaro; Yunokawa, Mayu; Tamura, Kenji; Tamura, Tomohide; Minami, Hironobu; Koh, Yasuhiro; et al.
Abstract : Methods for the enumeration and molecular characterization of circulating tumor cells (CTC) have been actively investigated. However, such methods are still technically challenging. We have developed a novel epithelial cell adhesion molecule independent CTC enumeration system integrated with a sorting system using a microfluidics chip. We compared the number of CTC detected using our system with those detected using the CellSearch system in 46 patients with various cancers. We also evaluated epidermal growth factor receptor (EGFR) and PIK3CA mutations of captured CTC in a study of 4 lung cancer and 4 breast cancer patients. The percentage of samples with detected CTC was significantly higher with our system (65.2%) than with CellSearch (28.3%). The number of detected CTC per patient using our system was statistically higher than that using CellSearch (median 5, 0; P = 0.000172, Wilcoxon test). In the mutation analysis study, the number of detected CTC per patient was low (median for lung, 4.5; median for breast, 5.5); however, it was easy to detect EGFR and PIK3CA mutations in the CTC of 2 lung and 1 breast cancer patient, respectively, using a commercially available kit. Our system is more sensitive than CellSearch in CTC enumeration of various cancers and is also capable of detecting EGFR and PIK3CA mutations in the CTC of lung and breast cancer patients, respectively. Abstract : This novel CTC system performed superior sensitivity in CTC detection compared with CellSearch in various cancer patients. EGFR and PIK3CA mutation are detected from captured CTC in lung and breast cancer patients, respectively.